PENENTUAN SETTING OPTIMAL MESIN 3D PRINTER BERBASIS FUSED DEPOSITION MODELING MENGGUNAKAN METODE TAGUCHI - Prakasa, Anggit; Sutisna, Setya Permana; Ahmad, Anton Royanto (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
The 3D printers process is applied to create prototype components, but at the last 3D Printers are often applied as last products. So, high accuracy is required in this case. In this research will find the optimalsetting of the dimensional accuracy 3D printers based fused deposition modeling. The method used isthe Taguchi method, the reason for using this method its efficiency, this is because the OrthogonalArray matrix requires less number of experiments than the classical experimental design. Analysis ofVariance is also needed in this method to see the factors that significantly influence the responsevariable. The results of this study indicate that the factors that significantly influence is printspeed bycontributing 53.08%, flowrate contributes 16.4%, and temperature heater block contributes 3.85% andoptimal setting is temperature heater block 190º, print speed 60mm/s and flowrate 6.28 mm3/s. (A1,C3 dan D2).